Lateral Habenula Responses During Eye Contact in a Reward Conditioning Task - Lee, Hyunchan; Hikosaka, Okihide (Frontiers in Behavioral Neuroscience, 2022)
For many animals, social interaction may have intrinsic reward value over and above its utility as a means to the desired end. Eye contact is the starting point of interactions in many social animals, including primates, and abnormal patterns of eye contact are present in many mental disorders. Whereas abundant previous studies have shown that negative emotions such as fear strongly affect eye contact behavior, modulation of eye contact by reward has received scant attention. Here we recorded eye movement patterns and neural activity in lateral habenula while monkeys viewed faces in the context of Pavlovian and instrumental conditioning tasks. Faces associated with larger rewards spontaneously elicited longer periods of eye contact from the monkeys, even though this behavior was not required or advantaged in the task. Concurrently, lateral habenula neurons were suppressed by faces signaling high value and excited by faces signaling low value. These results suggest that the reward signaling of lateral habenula may contribute to social behavior and disorders, presumably through its connections with the basal ganglia.